Application of uniform asymptotics method to analyzing the asymptotic behaviour of the general fourth Painlevé transcendent. (12th July 2005) - Qin, Huizeng; Lu, Youmin
Abstract : We use the uniform asymptotics method proposed by A. P. Bassom et al. (1998) to study the general fourth Painlevé transcendent, find a group of its asymptotics and the corresponding monodromic data, and prove its existence and "uniqueness."